2018
DOI: 10.1001/jamaneurol.2018.0345
|View full text |Cite
|
Sign up to set email alerts
|

Discovering New Benefits From Old Drugs With Big Data—Promise for Parkinson Disease

Abstract: 8.Simner PJ, Miller S, Carroll KC. Understanding the promises and hurdles of metagenomic next-generation sequencing as a diagnostic tool for infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The study observed a 28% higher incidence rate of PD in IBD patients than in unaffected matched controls. In IBD patients, anti-TNF treatment resulted in 78% reduction in the rate of PD incidence relative to patients that did not receive the treatment [ 120 , 121 ]. A similar approach was reported by Slade et al They conducted experiments on rats to investigate the effects of Attention Deficit Hyperactivity Disorder (ADHD) medication (type and timing) on the “rats’ propensity to exhibit addiction-like behavior”, which led to the hypothesis that initiating ADHD medication in adolescence “may increase the risk for SUD in adulthood”.…”
Section: Existing Solutionsmentioning
confidence: 99%
“…The study observed a 28% higher incidence rate of PD in IBD patients than in unaffected matched controls. In IBD patients, anti-TNF treatment resulted in 78% reduction in the rate of PD incidence relative to patients that did not receive the treatment [ 120 , 121 ]. A similar approach was reported by Slade et al They conducted experiments on rats to investigate the effects of Attention Deficit Hyperactivity Disorder (ADHD) medication (type and timing) on the “rats’ propensity to exhibit addiction-like behavior”, which led to the hypothesis that initiating ADHD medication in adolescence “may increase the risk for SUD in adulthood”.…”
Section: Existing Solutionsmentioning
confidence: 99%
“…4 Repurposing existing drugs represents an attractive alternative to traditional drug development. 5…”
Section: Introductionmentioning
confidence: 99%
“…4 Repurposing existing drugs represents an attractive alternative to traditional drug development. 5 We have conducted hypothesis-free analyses using data from Norwegian health registries to evaluate associations between any of the drugs used in Norway over a period of 15 years and the risk of developing PD. In a previous study, we linked drug effects demonstrated through experiments in cells and animals to corresponding associations in humans using these registries.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that the induction of PD-like symptoms in humanized CD34 + mice using MPTP can cause an associated neuroinflammatory response that was attenuated using FK506, an immunosuppressant drug. Based on these and other studies, it has been suggested that anti-inflammatory medications may have utility in PD [16][17][18][19][20]. In fact, one recent study demonstrated that probiotic intake impacted inflammatory gene expression in PD patients after 12-weeks [21] with another showing that probiotic supplementation reduced inflammation and decreased MDS-UPDRS scores [22].…”
Section: Introductionmentioning
confidence: 99%